Polyimide modified nanofiber diaphragm composite gel polymer electrolyte and preparation method thereof

By using polyimide-modified nanofiber separator composite gel polymer electrolyte in lithium-ion batteries, the problems of weak mechanical properties and low ionic conductivity of gel polymer electrolyte are solved, and the battery performance and safety are improved.

CN119742432AActive Publication Date: 2025-04-01TONGJI UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411738375.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Gel polymer electrolytes have problems such as low transfer number of lithium ion, poor thermal stability, and weak mechanical properties in lithium-ion batteries, resulting in limited battery performance and energy density.

Method used

Polyolefin nanofibers were prepared by coextrusion technology and modified into polyimide modified nanofiber separators, which were compounded in polyethylene oxide gel electrolyte to form a composite film to improve mechanical properties and ionic conductivity.

Benefits of technology

It significantly improves the mechanical properties of the separator, reduces the thickness of the gel polymer electrolyte, and maintains excellent ionic conductivity and battery performance, effectively solving safety problems such as liquid leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742432A_ABST
    Figure CN119742432A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a polyimide modified nanofiber diaphragm composite gel polymer electrolyte, which comprises the following steps: preparing a polyimide surface modified polyolefin nanofiber diaphragm, and dissolving polyethylene oxide by using an organic solvent to obtain a polyelectrolyte casting solution; soaking the polyimide surface modified polyolefin nanofiber diaphragm into a polyelectrolyte membrane casting solution to obtain a composite membrane, and finally soaking the composite membrane into an electrolyte for activation to obtain the polyimide modified nanofiber diaphragm composite gel polymer electrolyte. The polyimide modified nanofiber diaphragm composite gel polymer electrolyte prepared by the invention has excellent ionic conductivity and battery cycle performance, meanwhile, the preparation process is simple and efficient, the cost is low, the safety performance is remarkably improved, and the development and application of a new generation of gel electrolyte lithium ion batteries are further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery gel polymer electrolyte, and in particular to a polyimide modified nanofiber diaphragm composite gel polymer electrolyte and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are the most popular energy storage system currently used. Due to their high energy density, long cycle life, and low self-discharge rate, they are widely used in electric vehicles, electric bicycles, and various portable electronic devices. Despite this, liquid electrolytes generally use alkyl carbonates as organic solvents. This carbonate liquid electrolyte will have excessive parasitic reactions with the highly reactive lithium metal, resulting in continuous deterioration of battery cycle performance. At the same time, the low flash point, low boiling point, and uncontrolled lithium dendrite growth of this organic solvent can cause combustion or even explosion under certain conditions, and there is a risk of electrolyte leakage, which poses certain safety hazards.

[0003] Compared with liquid electrolytes, solid polymer electrolytes (SPE) and gel polymer electrolytes (GPE) have great advantages in terms of safety performance. Although solid electrolytes have high energy density and can meet the use requirements of flexible portable devices, their low ionic conductivity limits their application to a certain extent. Gel polymer electrolytes refer to semi-solid electrolytes formed by the swelling of solid polymers in solvents. At low polymer matrix content, they can not only make the room temperature conductivity of lithium-ion batteries reach 10 -3 S cm -1 , while also having excellent safety performance.

[0004] However, gel polymer electrolytes still have a series of problems such as low lithium ion transfer number, poor thermal stability, and weak mechanical properties. Researchers usually add plasticizers or liquid electrolytes to improve the ionic conductivity of gel electrolytes, but at the same time they reduce the mechanical properties of gel electrolytes. Therefore, gel electrolytes without additional supporting substrates often have a larger thickness and a relatively high polymer matrix content in order to ensure their mechanical integrity, but this also damages the battery performance and energy density of gel electrolytes. Summary of the invention

[0005] The present invention is made to solve the above problems, and aims to provide a polyimide modified nanofiber diaphragm composite gel polymer electrolyte and a preparation method thereof.

[0006] The present invention provides a method for preparing a polyimide modified nanofiber membrane composite gel polymer electrolyte, which has the following characteristics and specifically comprises the following steps: S1, obtaining polyolefin nanofibers by co-extrusion technology, and grading and sieving the polyolefin nanofibers, and then dispersing the polyolefin nanofibers with uniform size and suitable diameter in a solvent and filtering them to obtain a polyolefin nanofiber membrane; S2, diluting a polyimide solution, soaking the polyolefin nanofiber membrane in the polyimide solution, taking it out after 20-40 minutes, and placing it in a vacuum oven at 60-100°C to fully dry to remove excess solvent, and obtaining a polymer modified polyolefin nanofiber membrane. Membrane; S3, adding polyethylene oxide to an organic solvent containing a plasticizer, stirring until completely dissolved to prepare a solution, then adding lithium salt, continuing to stir until fully mixed, to obtain a polyelectrolyte casting solution; S4, infiltrating the polymer-modified polyolefin nanofiber diaphragm into the polyelectrolyte casting solution, taking it out after 3-5 minutes, placing it in a vacuum oven and fully drying it to remove excess solvent, to obtain a composite membrane; S5, placing the composite membrane in an inert atmosphere glove box, immersing it in the electrolyte for full activation, taking it out after 1-3 hours, and using paper to completely absorb the surface electrolyte to obtain a polyimide-modified nanofiber diaphragm composite gel polymer electrolyte with a thickness of 20-35μm.

[0007] The polyimide modified nanofiber membrane composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein the polyolefin nanofiber material in step S1 is one or more of high-density polyethylene, low-density polyethylene, polyethylene, polypropylene, modified polypropylene and modified polyethylene.

[0008] The polyimide modified nanofiber diaphragm composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein, the mesh number of the intermediate screening in step S1 is 100-400 meshes.

[0009] The polyimide-modified nanofiber membrane composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein the solvent type used for the polyimide in step S2 is one or more of ethanol, tetrahydrofuran, N-methylpyrrolidone and N,N-dimethylformamide.

[0010] The polyimide modified nanofiber separator composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein the mass concentration of the polyimide solution in step S2 is 1-20%.

[0011] The polyimide modified nanofiber membrane composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein the plasticizer selected in step S3 is one or more of propylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and carbonate esters.

[0012] In the polyimide modified nanofiber diaphragm composite gel polymer electrolyte provided by the present invention, it can also have the following characteristics: wherein the type of organic solvent in step S3 is a mixture of one or more of ether, ethyl acetate, n-propanol, acetone and petroleum ether, and the lithium salt is one or more of lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium hexafluoroarsenate.

[0013] The polyimide modified nanofiber membrane composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein the drying temperature in the vacuum oven in step S4 is 60-80°C.

[0014] The polyimide modified nanofiber diaphragm composite gel polymer electrolyte provided by the present invention may also have the following characteristics: wherein, in step S5, the electrolyte is ethylene carbonate, dimethyl carbonate, propylene carbonate and lithium hexafluorophosphate, wherein ethylene carbonate: dimethyl carbonate: propylene carbonate = 1: (0.8-1.2): (0.8-1.2) Vol%, and the lithium hexafluorophosphate is 0.8-1.2M.

[0015] The present invention also provides a polyimide modified nanofiber membrane composite gel polymer electrolyte, which has the following characteristics: it is prepared by the above-mentioned preparation method of the polyimide modified nanofiber membrane composite gel polymer electrolyte.

[0016] Functions and Effects of the Invention

[0017] According to the polyimide-modified nanofiber diaphragm composite gel polymer electrolyte and its preparation method, the present invention provides an effective strategy for balancing the mechanical integrity and ionic conductivity of the gel polymer electrolyte. The polyolefin nanofibers are successfully modified by polyimide and compounded with polyethylene oxide gel electrolyte. The bonding effect between the modified nanofibers is significantly enhanced, which effectively improves the mechanical properties of the diaphragm, enabling it to be used as a strong porous substrate to support the gel polymer electrolyte, greatly reducing the thickness of the gel polymer electrolyte. At the same time, compared with commercial diaphragms of the same material, the polyolefin nanofiber diaphragm has a higher porosity and dimensional stability, which is more conducive to the uniform penetration of the polymer matrix, provides a stable channel for the transmission of lithium ions, and can effectively inhibit the growth of dendrites. In addition, this preparation method also provides a new safety strategy for liquid electrolyte batteries. Through the compounding of gel polymer electrolytes, while retaining excellent ionic conductivity and battery performance, it effectively solves safety issues such as liquid leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the mechanical property image of the gel electrolyte of Example 1 and Comparative Examples 1-2 of the present invention;

[0019] Figure 2 The AC impedance spectra of the gel electrolytes of Examples 1-5 and Comparative Example 1 of the present invention assembled into stainless steel-to-stainless steel batteries;

[0020] Figure 3 The rate performance of the battery assembled with the gel electrolytes of Examples 1 to 3 and Comparative Example 1 of the present invention; and

[0021] Figure 4 The cycle performance of the battery assembled with the gel electrolyte of Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following embodiments and drawings specifically describe a polyimide-modified nanofiber diaphragm composite gel polymer electrolyte and a preparation method thereof.

[0023] A method for preparing a polyimide modified nanofiber diaphragm composite gel polymer electrolyte comprises the following steps:

[0024] S1. Prepare 8192-32768 layers of polyolefin nanofibers by co-extrusion technology, with a processing temperature of 150-200°C and an extrusion speed ratio of 1:1 between the two extruders; then fully disperse the polyolefin nanofibers in anhydrous ethanol, filter through a 100-500 mesh stainless steel sieve to remove excess impurities at the coarser fiber level, and finally collect the fibers in the filtrate and filter them in a negative pressure filtration device to form a diaphragm with a diameter of 4-10 cm, and control the diaphragm thickness to be 15-30 μm.

[0025] S2. Use N-methylpyrrolidone solution to dilute 5 mM polyimide solution, and soak the polyolefin nanofiber membrane prepared in S1 in polymer solutions of different concentrations. Take it out after 30 minutes, place it in a vacuum oven at 100°C to fully dry to remove excess solvent, and obtain nanofiber composite membranes with different polyimide loading amounts.

[0026] S3. Weigh 0.8-1.0 g of polyethylene oxide, and then weigh 20 ml of organic solvent and add them into a round-bottom flask. Fully mix the polyethylene oxide and the organic solvent, and add 0.05 ml of plasticizer and 0.4 g of lithium salt, and heat and stir. The heating temperature is 50° C., the stirring speed is 150 rpm, and the reaction is carried out for 30 minutes to obtain a polymer electrolyte casting solution.

[0027] S4. The diaphragm prepared in S2 and the polymer electrolyte casting solution of S3 are compounded by an infiltration casting method, and after being fully dried in a vacuum oven at 60° C., a composite membrane of a polyimide-modified polyolefin nanofiber diaphragm and a polyethylene oxide gel electrolyte is obtained.

[0028] S5. Place the composite membrane obtained in S4 in a glove box filled with argon atmosphere, immerse it in an electrolyte (EC:DMC:PC=1:1:1Vol%, 1M LiPF6) for activation, take it out after 2 hours, absorb the surface electrolyte with filter paper, and obtain a polyimide-modified polyolefin nanofiber composite polyethylene oxide gel electrolyte.

[0029] Example 1

[0030] S1. Prepare 16384 layers of polyolefin nanofibers by co-extrusion technology, with a processing temperature of 200°C and an extrusion speed ratio of 1:1 between the two extruders; then fully disperse the polyolefin nanofibers in anhydrous ethanol, filter through 200-mesh and 300-mesh stainless steel sieves to remove excess impurities at the coarser fiber level, and finally collect the fibers in the filtrate and filter them in a negative pressure filtration device to form a diaphragm with a diameter of 6 cm, and control the diaphragm thickness to 20 μm.

[0031] S2. Use N-methylpyrrolidone solution to dilute the 5mM polyimide solution with a dilution ratio of 3%, and soak the polyolefin nanofiber membrane prepared in S1 in polymer solutions of different concentrations. After 30 minutes, take it out and place it in a vacuum oven at 100°C to fully dry to remove excess solvent, thereby obtaining nanofiber composite membranes with different polyimide loading amounts.

[0032] S3. Weigh 0.9 g of polyethylene oxide, and then weigh 20 ml of acetone and add them into a round-bottom flask. Mix the polyethylene oxide and acetone thoroughly, and add 0.05 ml of propylene carbonate and 0.4 g of lithium bis(trifluoromethanesulfonyl)imide, and heat and stir. The heating temperature is 50°C, the stirring speed is 150 rpm, and the reaction is carried out for 30 minutes to obtain a polymer electrolyte casting solution.

[0033] S4. The diaphragm prepared in S2 and the polymer electrolyte casting solution of S3 are compounded by an infiltration casting method, and after being fully dried in a vacuum oven at 60° C., a composite membrane of a polyimide-modified polyolefin nanofiber diaphragm and a polyethylene oxide gel electrolyte is obtained.

[0034] S5. Place the composite membrane obtained in S4 in a glove box filled with argon atmosphere, immerse it in an electrolyte (EC:DMC:PC=1:1:1Vol%, 1M LiPF6) for activation, take it out after 2 hours, absorb the surface electrolyte with filter paper, and obtain a polyimide-modified polyolefin nanofiber composite polyethylene oxide gel electrolyte.

[0035] Example 2

[0036] In this embodiment, based on the preparation conditions of Example 1, 16384 layers of polypropylene alternating fibers are replaced by 16384 layers of high-density polyethylene alternating fibers, the processing temperature is replaced by 160°C, and the diaphragm with a diameter of 6 cm and a thickness of 20 μm is replaced by a diaphragm with a thickness of 8 cm and 22 μm; the immersion in a 3% dilution ratio polyimide solution in step S2 is replaced by immersion in a 5% dilution ratio polyimide solution; in step S3, 0.9 g of polyethylene oxide is replaced by 1.0 g of polyethylene oxide, acetone is replaced by n-propanol, and propylene carbonate is replaced by ethylene carbonate.

[0037] Example 3

[0038] In this embodiment, based on the preparation conditions of Example 1, the diaphragm with a diameter of 6 cm and a thickness of 20 μm is replaced by a diaphragm with a diameter of 8 cm and a thickness of 22 μm; in step S3, 0.9 g of polyethylene oxide is replaced by 1.0 g of polyethylene oxide, acetone is replaced by ether, propylene carbonate is replaced by ethylene carbonate, and lithium bistrifluoromethanesulfonimide is replaced by lithium hexafluorophosphate.

[0039] Example 4

[0040] In this embodiment, based on the preparation conditions of Example 1, the diaphragm with a diameter of 6 cm and a thickness of 20 μm is replaced by a diaphragm with a diameter of 6 cm and a thickness of 15 μm; the immersion in a polyimide solution with a dilution ratio of 3% in step S2 is replaced by immersion in a polyimide solution with a dilution ratio of 5%; in step S3, acetone is replaced by ether, propylene carbonate is replaced by ethylene carbonate, and lithium bistrifluoromethanesulfonyl imide is replaced by lithium hexafluorophosphate.

[0041] Example 5

[0042] In this embodiment, based on the preparation conditions of Example 1, the diaphragm with a diameter of 6 cm and a thickness of 20 μm is replaced by a diaphragm with a diameter of 6 cm and a thickness of 15 μm; in step S3, 0.9 g of polyethylene oxide is replaced by 1.0 g of polyethylene oxide, acetone is replaced by ether, propylene carbonate is replaced by ethylene carbonate, and lithium bistrifluoromethanesulfonimide is replaced by lithium hexafluorophosphate.

[0043] Comparative Example 1

[0044] 16384 layers of polypropylene nanofibers were prepared by nanolayer co-extrusion technology. The processing temperature was 200℃ and the extrusion speed ratio of the two extruders was 1:1. The crushed fibers were then immersed in anhydrous ethanol and filtered through a 300-mesh stainless steel sieve to remove excess impurities at the coarser fiber level. Finally, the fibers in the filtrate were collected and filtered into a diaphragm with a diameter of 6 cm in a negative pressure filtration device. The diaphragm thickness was controlled at 25μm.

[0045] S2. Weigh 0.9 g of polyethylene oxide, and then weigh 20 ml of acetone and add them into a round-bottom flask. Mix the polyethylene oxide and the organic solvent thoroughly, and add 0.05 ml of propylene carbonate and 0.4 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to heat and stir. The heating temperature is 50°C, the stirring speed is 150 rpm, and the reaction is carried out for 30 minutes to obtain a polymer electrolyte casting solution.

[0046] S3. The diaphragm prepared in S1 and the polymer electrolyte casting solution of S2 are compounded by an infiltration casting method, and after being fully dried in a vacuum oven at 60° C., a composite membrane of a polypropylene nanofiber diaphragm and a polyethylene oxide gel electrolyte is obtained.

[0047] S4. Place the composite membrane obtained in S3 in a glove box filled with argon atmosphere, immerse it in an electrolyte (EC:DMC:PC=1:1:1Vol%, 1M LiPF6) for activation, take it out after 2 hours, absorb the surface electrolyte with filter paper, and obtain a polypropylene nanofiber composite polyethylene oxide gel electrolyte.

[0048] Comparative Example 2

[0049] Weigh 0.9 g of polyethylene oxide and 20 ml of acetone into a round-bottom flask, mix the polyethylene oxide and the organic solvent thoroughly, add 0.05 ml of propylene carbonate and 0.4 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), heat and stir at 50 ° C, stir at 150 rpm, and react for 30 min to obtain a polymer electrolyte casting solution.

[0050] S2. Pour the casting liquid into the mold and let it stand for 10 minutes, then put it into a 60°C vacuum oven and fully dry it to obtain a polyethylene oxide gel film.

[0051] S3. Place the composite membrane obtained in S2 in a glove box filled with argon atmosphere, immerse it in an electrolyte (EC:DMC:PC=1:1:1Vol%, 1M LiPF6) for activation, take it out after 2 hours, absorb the surface electrolyte with filter paper, and obtain a polyethylene oxide gel electrolyte.

[0052] Figure 1 It is the mechanical property image of the gel electrolyte of Example 1 of the present invention and Comparative Examples 1-2. Figure 2 The AC impedance spectra of Examples 1-5 and Comparative Example 1 of the present invention are those of stainless steel versus stainless steel batteries.

[0053] like Figure 1 As shown, the gel electrolytes prepared in Example 1 and Comparative Examples 1-2 both exhibit good flexibility, but the gel electrolyte prepared in Comparative Example 2 exhibits poor mechanical properties due to the lack of internal support of a strong porous substrate. The maximum tensile stress of the gel electrolyte supported by the strongly porous modified nanofiber diaphragm prepared in Example 1 is 18.12 MPa, and the gel thickness is greatly improved (reduced from 150 μm to 25 μm).

[0054] like Figure 2 As shown, the polyimide modified nanofiber membrane prepared by the present invention conforms to the gel polymer electrolyte and exhibits higher ionic conductivity. Examples 1-5 and Comparative Example 1 all exhibit good ionic conductivity. Compared with Comparative Example 2 of the same thickness, a short circuit phenomenon is exhibited. This is attributed to the membrane acting as a supporting structure internally, while the pure polyethylene oxide gel electrolyte is too thin and has insufficient mechanical strength, resulting in a short circuit.

[0055] Examples 1-3 and Comparative Example 1 were assembled into lithium-ion batteries and their performance was tested. 0.8 Co 0.1 Mn 0.1O2 (NCM811) was used as the positive electrode material, graphite as the negative electrode material, and the electrolyte was a 1M lithium hexafluorophosphate (LiPF6) solution, in which the solvent was a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1. The electrochemical test was carried out on the Xinwei battery test system.

[0056] Figure 3 The gel electrolytes of Examples 1-3 and Comparative Example 1 of the present invention are assembled into rate performance of batteries. Figure 4 The cycle performance of the battery assembled with the gel electrolyte of Example 1 and Comparative Example 1 of the present invention.

[0057] like Figure 3 , 4 As shown, the polyimide modified nanofiber diaphragm composite gel polymer electrolyte prepared by the present invention exhibits excellent electrochemical performance. For example, when the current density reaches 5C, Example 1 still has a high specific capacity (80mAh / g), while Examples 2 and 3 have a certain impact on battery performance due to the clogging of the diaphragm pores by the concentration of the polyimide solution and the increase in the thickness of the diaphragm. Compared with Comparative Example 1, having a diaphragm as a supporting structure can significantly improve the high-rate performance of the battery. At the same time, the battery prepared in Example 1 has a higher capacitance retention rate (91.3%) than Comparative Example 1 (79.2%) after 150 cycles of charge and discharge, showing excellent cycle stability.

[0058] In summary, the polyimide modified nanofiber membrane composite gel electrolyte prepared by the present invention has excellent performance, low cost, and significantly improved safety performance, which is conducive to further promoting the development and application of a new generation of gel electrolyte lithium-ion batteries.

[0059] Functions and Effects of the Embodiments

[0060] According to the polyimide-modified nanofiber diaphragm composite gel polymer electrolyte and its preparation method, the present invention provides an effective strategy for balancing the mechanical integrity and ionic conductivity of the gel polymer electrolyte. The polyolefin nanofibers are successfully modified by polyimide and compounded with polyethylene oxide gel electrolyte. The bonding effect between the modified nanofibers is significantly enhanced, which effectively improves the mechanical properties of the diaphragm, enabling it to be used as a strong porous substrate to support the gel polymer electrolyte, greatly reducing the thickness of the gel polymer electrolyte. At the same time, compared with commercial diaphragms of the same material, the polyolefin nanofiber diaphragm has a higher porosity and dimensional stability, which is more conducive to the uniform penetration of the polymer matrix, provides a stable channel for the transmission of lithium ions, and can effectively inhibit the growth of dendrites. In addition, this preparation method also provides a new safety strategy for liquid electrolyte batteries. Through the compounding of gel polymer electrolytes, while retaining excellent ionic conductivity and battery performance, it effectively solves safety issues such as liquid leakage.

[0061] The present invention uses nanolayer co-extrusion technology to prepare polyolefin nanofibers with uniform size, excellent porosity and strong electrolyte affinity, and then filters them into membranes. The polyolefin nanofibers are immersed in polyimide solutions of different concentrations through a solution infiltration method. After a certain period of infiltration, the excess solvent is removed by vacuum drying, thereby completing the surface modification of the polyolefin nanofibers. This allows the diaphragm to maintain excellent porosity and wettability while greatly improving its own mechanical strength.

[0062] The present invention adds an additional high-strength porous membrane to the gel polymer electrolyte, providing an effective strategy to balance the mechanical integrity and ionic conductivity of the gel polymer electrolyte. Compared with commercial membranes, polyolefin nanofiber membranes have higher porosity and electrolyte permeability, which is more conducive to the uniform penetration of the polymer matrix and provides a stable medium for the transmission of lithium ions. At the same time, the polyimide-modified polyolefin nanofiber membrane exhibits excellent mechanical properties and can effectively reduce the thickness of the gel polymer electrolyte, which is far lower than the widely used 120 to 200 μm, making the room temperature conductivity of the prepared gel polymer electrolyte not inferior to that of traditional liquid electrolytes.

[0063] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a polyimide modified nanofiber diaphragm composite gel polymer electrolyte, characterized in that: The specific steps include: S1, obtaining polyolefin nanofibers by co-extrusion technology, and classifying and sieving the polyolefin nanofibers, and then dispersing the polyolefin nanofibers with uniform size and suitable diameter in a solvent and filtering them to obtain a polyolefin nanofiber separator; S2, diluting the polyimide solution, immersing the polyolefin nanofiber membrane in the polyimide solution, taking it out after 20-40 minutes, placing it in a vacuum oven at 60-100° C. to fully dry it to remove excess solvent, and obtaining a polymer-modified polyolefin nanofiber membrane; S3, adding polyethylene oxide to an organic solvent containing a plasticizer, stirring until completely dissolved to prepare a solution, then adding lithium salt, and continuing to stir until fully mixed to obtain a polyelectrolyte casting solution; S4, soaking the polymer-modified polyolefin nanofiber separator into the polyelectrolyte casting solution, taking it out after 3-5 minutes, and placing it in a vacuum oven to fully dry to remove excess solvent, thereby obtaining a composite membrane; S5. Place the composite membrane in a glove box with an inert atmosphere, immerse it in an electrolyte for full activation, take it out after 1-3 hours, and use paper to completely absorb the surface electrolyte to obtain a polyimide-modified nanofiber diaphragm composite gel polymer electrolyte with a thickness of 20-35 μm.

2. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The polyolefin nanofiber material in step S1 is one or more of high-density polyethylene, low-density polyethylene, polyethylene, polypropylene, modified polypropylene and modified polyethylene.

3. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The mesh size of the intermediate screening in step S1 is 100-400 meshes.

4. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The solvent type used for the polyimide in step S2 is one or more of ethanol, tetrahydrofuran, N-methylpyrrolidone and N,N-dimethylformamide.

5. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The mass concentration of the polyimide solution in step S2 is 1-20%.

6. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The plasticizer selected in step S3 is one or more of propylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and esters of carbonate.

7. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The organic solvent type in step S3 is a mixture of one or more of diethyl ether, ethyl acetate, n-propanol, acetone and petroleum ether, and the lithium salt is one or more of lithium hexafluorophosphate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium hexafluoroarsenate.

8. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, The drying temperature of the vacuum oven in step S4 is 60-80°C.

9. The method for preparing the polyimide modified nanofiber separator composite gel polymer electrolyte according to claim 1, characterized in that: in, In the step S5, the electrolyte is ethylene carbonate, dimethyl carbonate, propylene carbonate and lithium hexafluorophosphate, wherein the ethylene carbonate: dimethyl carbonate: propylene carbonate = 1: (0.8-1.2): (0.8-1.2) Vol%, and the lithium hexafluorophosphate is 0.8-1.2M.

10. A polyimide modified nanofiber membrane composite gel polymer electrolyte, characterized in that: The composite gel polymer electrolyte is prepared by the method for preparing the polyimide modified nanofiber diaphragm according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite diaphragm, preparation method thereof and lithium ion battery

    CN104088155A

  • Preparation method for crosslinked polyimide gel polymer electrolyte membrane

    CN106328862A

  • Composite lithium ion battery diaphgrm and preparation method thereof

    CN108346765A

  • Polyimide microsphere slurry, composite separator and lithium ion battery

    CN109817870A

  • Multi-hydrogen-bond cross-linked cellulose / carboxylated polyimide nanofiber composite diaphragm as well as preparation method and application of multi-hydrogen-bond cross-linked cellulose / carboxylated polyimide nanofiber composite diaphragm

    CN113471628A